Myths in advertising: Current interpretations of ancient tales - Rubio-Hernández, Maria del Mar (Academic Quarter | Akademisk kvarter, 2011)
The starting point of Myths in advertising: current interpretations of ancient tales by María del Mar Rubio-Hernández is that despite the influence of science and technology in today’s world, there are still myths that play a critical role in our social imaginary and many of which have different modern manifestations. According to Rubio-Hernández, mass media today could be highlighted as the most efficient vehicle that transmits myths in our culture, since mass media do not only extend those narratives, but also amplify them. Her article specifically focuses on the presence of myths seen in advertisements, and she argues that advertising utilizes elements which are in the collective imaginary, and consequently are already settled in the audience’s mind, guaranteeing its recognition and identification.